Effects of single/compound pit texture on the friction-induced vibration and noise of thrust cylindrical roller bearings - Wang, Yueyong (Strojniški vestnik, 2023)
To improve the reliability and service life of thrust cylindrical roller bearings (TCRBs), the effects of single/compound pit texture on tribological properties and on friction-induced vibration and noise were studied. Laser marking equipment was used to create compound pit texture on a shaft washer. A universal friction and wear test rig was used to measure the friction force, vibration acceleration, and noise signals of TCRBs. The differences between the single/composite pit-textured and non-textured surfaces were studied in terms of the friction, wear, and vibration noise properties. The results revealed that the friction force and wear loss of the single/composite pit-textured surface were markedly lower than those of the non-textured surface. Compared to non-textured surface bearings, the friction force and wear loss for textured surface bearings were reduced by 39.6 % and 59.6 %, respectively, when the diameter, depth, and area density of the pit were 300 µm, 10 µm, and 10 %, respectively. The single/composite pit-textured surface exhibited good potential for vibration absorption and noise suppression. It could effectively interfere with the self-excited vibration of the TCRBs friction pair system, thereby reducing the degree of vibration noise of the TCRBs.
Keywords: compound pit texture; enostavna teksturirana površina; friction force; friction-induced vibration; hrup zaradi trenja; noise; obraba; sestavljena teksturirana površina; single pit texture; thrust cylindrical roller bearings; torna sila; valjčni aksialni ležaj; vibracije; wear